ANALISIS PERAN PENDANAAN DAERAH UNTUK SEKOLAH DASAR MELALUI PENGHITUNGAN UNIT COST DI KOTA MAGELANG - Andjar Prasetyo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
This study aims to determine and analyze the scale unit cost of primary school students in in Magelang City. Methods using multiple regression analysis with independent variables that salaries of teachers and personnel, Material Costs and Operational, Administrative Costs and Fees Investment and the dependent variable Number of primary school Graduates. Location of the study conducted in 59 elementary schools in Magelang City with the details in 17 elementary school on South Magelang District, Central District of Magelang as much as 24 primary schools and District of North Magelang as much as 18 primary schools. Assumptions calculation of the number of students from the level or grade one to grade six to the budget used by calculating the regression. Regression results obtained Y = 62.047 - 0,090gaguper 2,737bimo + 0,956binves +0,723biad. The calculation of unit cost in primary education per student each institution and elementary school (SD) based on minimum service standards for the provision of basic education in the city of Magelang at 6.204.653(IDR), - per year, or 517.054(IDR), - per month. The value of the unit cost in practice is not only enjoyed by students from the City of Magelang but comes also from outside the City of Magelang.